Managing Intraorganizational Diffusion of Innovations Impact of Buying Center Dynamics and Environments - PAE, Jae H. (Institutional Knowledge at Singapore Management University, 2002)
Companies often introduce organizational innovations into their corporate environment with the aim of improving their operational efficiencies. While this practice has become a well-accepted percept among both practitioners and academics over the years for its intuitive appeal, there is an increasing evidence to suggest that companies often fail to fully capitalize on the adopted innovation throughout their organizations. To this end, this study sets out to identify the factors that play a tangible role in facilitating the intraorganizational diffusion of innovations. In this context, we not only examine the roles of buying center dynamics and environments in the intraorganizational diffusion process but also assess the impact on the innovation-adopting firm through the high level of intraorganizational diffusion.